Longipedia coronata Claus 1863 ... - Apostolov, Apostol (Zenodo, 2014)
Longipedia coronata Claus, 1863 Material examined: St. 717 (2 ♀♀) bottom of gravel. Distribution in Iceland: Icelandic shore of the Atlantic Ocean. ... : Published as part of Apostolov, Apostol, 2014, Contribution to the study of marine harpacticoid fauna (Crustacea, Copepoda) of Iceland, pp. 1-5 in ZooNotes 62 (62) on page 2, DOI: 10.5281/zenodo.8298375 ...